2014
DOI: 10.4143/crt.2014.46.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocirrhosis of Breast Cancer Metastases to the Liver Treated by Chemotherapy

Abstract: Pseudocirrhosis refers to a condition that shows changes in hepatic contour that mimic cirrhosis radiographically in the absence of the typical histopathological findings of cirrhosis. This condition has been observed in patients with cancer metastatic to the liver, both in those who have undergone prior systemic chemotherapy and those who have not. Pseudocirrhosis may cause difficulty in interpretation of the response to chemotherapy and hepatic decompression and complication of portal hypertension have a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…Although there were no data confirming that the patient had the UGT1A9 polymorphism, it was hypothesized that these genetic polymorphisms confer a clinical benefit but induce severe toxicity in the patient. Similar changes on imaging were previously reported in breast cancer with multiple liver metastases (10,11) and other cancers with multiple liver metastases, including pancreatic (12), esophageal (13) and thyroid cancer (14). The morphological changes of the liver in these cases are referred to as 'pseudocirrhosis'.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Although there were no data confirming that the patient had the UGT1A9 polymorphism, it was hypothesized that these genetic polymorphisms confer a clinical benefit but induce severe toxicity in the patient. Similar changes on imaging were previously reported in breast cancer with multiple liver metastases (10,11) and other cancers with multiple liver metastases, including pancreatic (12), esophageal (13) and thyroid cancer (14). The morphological changes of the liver in these cases are referred to as 'pseudocirrhosis'.…”
Section: Discussionsupporting
confidence: 56%
“…Although the precise mechanism underlying the development of pseudocirrhosis remains unknown, the response to systemic chemotherapeutic agents may induce cirrhotic changes with tumor shrinkage following chemotherapy. Previous reports (10)(11)(12) have indicated that pseudocirrhosis may be associated with nodular regenerative hyperplasia (NRH) caused by chemotherapy-induced hepatic injury. NRH is characterized by widespread transformation of nor mal liver parenchyma into hyperplastic regenerative nodules without bridging fibrosis, a characteristic that distinguishes this entity from liver cirrhosis (15).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, suspected development of pseudocirrhosis at imaging in patients receiving chemotherapy must be communicated to the oncologist. While pseudocirrhosis typically occurs in the setting of positive treatment response, it can also occur with disease progression owing to infiltrating tumor, which can cause desmoplastic changes (52). MR imaging may help differentiate tumor response from progression, as the liver can become progressively heterogeneous with pseudocirrhosis at CT, limiting evaluation of disease burden.…”
Section: Hepatic Adverse Eventsmentioning
confidence: 99%
“…Despite its radiographic similarity to cirrhosis, pseudocirrhosis does not have histologic findings of regenerative nodules and bridging fibrosis, which are defining changes of true cirrhosis. The complications of cirrhosis, such as portal hypertension and ascites, are less common in pseudocirrhosis but do occur (31).…”
Section: Livermentioning
confidence: 99%